Etiology, treatment, and outcomes of status epilepticus episodes in the elderly - (:unkn) unknown (EGE UNIV, 2019)
Objective: Status epilepticus (SE) can cause life-threatening consequences. It is important to determine the etiologic factors of SE and treatment responses in elderly individuals, especially those with certain comorbidities. Based on our databank, these factors were evaluated in patients aged over 60 years. Methods: We reviewed the data of individuals aged over 60 years who were diagnosed clinically and electrophysiologically as having SE in the same databank. Demographic data of patients, SE subtypes, etiology, treatment responses, and survival of patients were noted. Results: We evaluated 162 patients aged older than 60 years with SE episodes. The mean age of the patients was 73 years. Seventy-three percent of the patients were female. The types of SE episodes were: nonconvulsive (NCSE) (93 episodes), convulsive SE (56 episodes), and NCSE after convulsive SE (23 episodes). Stroke was the leading cause of the etiologies and accounted for 37% of the SE episodes. The NCSE subtype was more refractory to treatment (p=0.003). The longer duration and refractoriness of the episodes significantly predicted a worse outcome (p=0.0001, p=0.01). Conclusion: Prolonged SE duration and the refractoriness of SE episodes are risk factors for poor outcomes.
Keywords: Elderly; etiology; outcome; status epilepticus; treatment; NONCONVULSIVE STATUS EPILEPTICUS; REFRACTORY STATUS EPILEPTICUS; DEFINITION; MINNESOTA; ROCHESTER; PROGNOSIS; EPILEPSY; CHILDREN; ADULTS; RISK